FACTORS INFLUENCING PHONEME MODIFICATION IN CONNECTED SPEECH - Tursunova Sharofat ,; Iskanova N.P, (TADQIQOTLAR.UZ, 2024)
Abstract Phoneme modification is a fascinating aspect of linguistics that involves the alteration of phonemes, the smallest units of sound in a language, when they are connected in speech. This phenomenon plays a crucial role in creating a fluid and effortless flow of communication. By examining the intricacies of phoneme modification, we can gain insights into the complexities of spoken language and appreciate the diversity of human communication. Modification of phonemes in connected speech is a fascinating area of study within the field of linguistics that explores how speech sounds change when spoken in continuous, connected utterances. This phenomenon plays a crucial role in our everyday communication, as it affects the clarity and intelligibility of spoken language.